(untitled) (Journal of Comparative & International Higher Education, 2023)
The aim of this study was to develop, with the participation of international students, the content of an online system that these students could use in the process of acculturation and adapting to a new environment. The action research with participatory design approach was selected as the research model from among the qualitative research methods and was implemented. Within the scope of the study, the topics that the students were interested with regard to Turkish culture, problems of adaptation to the Turkish culture and environment, and their expectations of the content of the online system to be developed were determined. These data were used to determine the main content heading of the online system. Later, the content development activities of the online system were carried out with the active participation of 18 international students.